Simulation in neurosurgical training: a blueprint and national approach to implementation for initial years trainees. (2nd September 2016) - Zhang, Lihan; Kamaly, Ian; Luthra, Pramod; Whitfield, Peter
Abstract: Simulation has played an increasing role in surgical training in recent years, this follows from various reports such as the Chief Medical Officer annual report and Sir John Temple's 'Time for Training' and also from other factors such as increasing focus on efficiency and transparency within the healthcare system. Evidence has shown that simulation can develop and improve technical, clinical, communication and management skills. With technological advances, the quality of simulation has also improved with more realistic models and environment. We have undertaken a review of recent drivers for simulation training in the UK, current techniques and have focused on the application of simulation training within the current UK Neurosurgical curriculum for newly appointed trainees.